A rare case of intravesical and urethral cystic Echinococcosis with multi-organ involvement from Türkiye - Tuna, Ayşegül; Topbaş, Emrah (The Journal of Infection in Developing Countries, 2025)
Introduction: Cystic echinococcosis is a parasitic disease recognized as a global public health problem in countries engaged in agriculture and animal husbandry. In natural life cycle, ungulates are intermediate hosts: canids are definitive hosts. It could be accidentally transmitted to humans by the fecal-oral route and migrate to the liver and other visceral organs to form cystic echinococcosis. It spreads hematogenously, lymphatically, and locally. The majority of initially asymptomatic patients develop liver and lung involvement. Involvement of other organs is rare. Cystic echinococcosis is a disease diagnosed by radiologic imaging and confirmed by histopathology, serologic, and molecular tests that can be used for diagnosis and follow-up primary and secondary infections. In this case report, the involvement of multiple and rare organs of cystic echinococcosis is presented. Case Presentation: An 82-year-old patient was admitted to the hospital with an inability to urinate. A glob vesicle was detected during examination, and urine output was achieved through urinary catheterization. Imaging techniques revealed multiple cysts in the abdomen, ureter, and bladder. Urine flow in ureter orifice was obstructed by cysts. Cystectomy was performed for the intraabdominal, intravesical, and ureteral cysts. Perioperative albendazole treatment was started as adjuvant and antiparasitic treatment was completed for one month. The case was confirmed histopathologically, and no secondary infection or complication was detected in one-year follow-up. Conclusions: By a multidisciplinary approach, the 82-year-old patient was diagnosed with Cystic echinococcosis, with a rare and multi-organ involvement, given the high risk of infection due to the environmental contamination in this country.